A highly Li+-conductive HfNb24O62 anode material for superior Li+ storage. Issue 4 (13th December 2019) - Fu, Qingfeng; Cao, Haijie; Liang, Guisheng; Luo, Lijie; Chen, Yongjun; Murugadoss, Vignesh; Wu, Shide; Ding, Tao; Lin, Chunfu; Guo, Zhanhu
Abstract : Highly Li + -conductive HfNb24 O62 is explored as a new intercalation-type anode material for fast-charging, large-capacity, safe and durable Li + storage. Abstract : Highly Li + -conductive HfNb24 O62 is explored as a new intercalation-type niobium-based oxide anode material for superior Li + storage. HfNb24 O62 owns a Wadsley–Roth shear structure with a large unit-cell volume, leading to a large Li + diffusion coefficient. HfNb24 O62 shows a large capacity, safe operating potential, high rate performance and good cyclability.